Altered reward expectancy in individuals with recent methamphetamine dependence. (January 2017) - Bischoff-Grethe, Amanda; Connolly, Colm G; Jordan, Stephan J; Brown, Gregory G; Paulus, Martin P; Tapert, Susan F; Heaton, Robert K; Woods, Steven P; Grant, Igor; ,
Background: Chronic methamphetamine use may lead to changes in reward-related function of the ventral striatum and caudate nucleus. Whether methamphetamine-dependent individuals show heightened reactivity to positively valenced stimuli (i.e. positive reinforcement mechanisms), or an exaggerated response to negatively valenced stimuli (i.e. driven by negative reinforcement mechanisms) remains unclear. This study investigated neural functioning of expectancy and receipt for gains and losses in adults with (METH+) and without (METH−) histories of methamphetamine dependence. Methods: Participants (17 METH+; 23 METH−) performed a probabilistic feedback expectancy task during blood-oxygen level-dependent (BOLD) functional magnetic resonance imaging (fMRI). Participants were given visual cues probabilistically associated with monetary gain, loss, or neutral outcomes. General linear models examined the BOLD response to: (1) anticipation of gains and losses, and (2) gain and loss monetary outcomes. Results: METH+ had less BOLD response to loss anticipation than METH− in the ventral striatum and posterior caudate. METH+ also showed more BOLD response to loss outcomes than to gain outcomes in the anterior and posterior caudate, whereas METH− did not show differential responses to the valence of outcomes. Discussion: METH+ individuals showed attenuated neural response to anticipated gains and losses, but their response to loss outcomes was greater than to gain outcomes. A decreased response to loss anticipation, along with a greater response to loss outcomes, suggests an altered ability to evaluate future risks and benefits based upon prior experience, which may underlie suboptimal decision-making in METH+ individuals that increases the likelihood of risky behavior.